RESILIENCE-GOVERNANCE AS A TOOL FOR ENHANCING THE STABILITY OF PUBLIC ADMINISTRATION IN THE NATIONAL SECURITY SECTOR OF UKRAINE - AVHUSTYN, Ruslan (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article delves into the critical concept of resilience-governance as a foundational tool for ensuring the sustainability and effectiveness of public administration within Ukraine’s national security sector. This is particularly crucial in the face of ongoing hybrid threats and protracted strategic instability, which challenge traditional bureaucratic models. The study argues that the conventional, rigid administrative structures are ill-equipped to handle the complex, multi-faceted nature of modern security challenges. Therefore, it is imperative to transform these models by adopting flexible, crisis-oriented, and network-based approaches. This paradigm shift is not merely about reacting to threats but about building an inherent capacity for adaptability, coordination, and responsiveness to a dynamic and unpredictable environment. The research provides a comprehensive analysis of the prerequisites for implementing a resilience-based governance model. It scrutinizes international experience and best practices, examining how various nations have successfully integrated resilience principles into their security frameworks. Concurrently, the study conducts a detailed review of Ukraine’s national legal frameworks, identifying both existing provisions that support this transformation and areas that require reform. It also investigates practical institutional shifts already underway, such as the decentralization of decision-making and the integration of new technologies, which lay the groundwork for a more resilient system. At the core of the article is the proposal of a comprehensive conceptual model of resilience-governance. This model is not a monolithic structure but an integrated system comprising several key functions. It emphasizes the pivotal role of digital transformation, not just as a technological upgrade, but as a means to enhance data sharing, situational awareness, and the speed of response. The model also highlights the importance of civic mobilization and engagement, recognizing that national security is a collective effort that extends beyond state institutions. By fostering collaboration with civil society, volunteer groups, and the private sector, the state can tap into a vast reservoir of resources and expertise. Furthermore, the model integrates strategic analytics as a core function. This involves leveraging advanced data analysis and forecasting to anticipate threats, identify vulnerabilities, and inform proactive policy decisions rather than simply reacting to events. Finally, the concept of institutional resilience is central, focusing on building the internal robustness of government bodies. This includes fostering a culture of continuous learning, cross-functional collaboration, and adaptive leadership. The findings and proposed model offer significant practical utility. The results of the study are intended to serve as a valuable resource for policymakers, government officials, and researchers involved in the development of public administration reform strategies. They provide concrete recommendations for strengthening national security systems and establishing effective mechanisms for responding to the nuanced and ever-evolving landscape of hybrid threats. This work underscores the need for a forward-looking, agile, and inclusive approach to governance that can not only withstand shocks but also emerge stronger from periods of profound instability.